Konsep Monoteisme Dalam Ṛgveda (Kajian Konsep Ketuhanan Hindu Perspektif Vedic Hermeneutic) - Ni Kadek Surpi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The Hindu concept of divinity is a fascinating discussion and always provokes a long debate. As the pioneers of Vedic studies in the modern age, Western writers have instilled that Hinduism adheres to a polytheistic system. It is considered a retarded ancient religion compared to the concept of Smith's religions that uphold monotheism, which is regarded as more plausible in the realm of modern human thinking. The Ṛgveda is the oldest text in human civilization, which is authoritatively considered to be the primary and first source of Hindu knowledge, including the concept of divinity. With the Vedic Hermeneutic pattern, this article examines the concept of monotheism in Ṛgveda, which is different from the concept of Western monotheism. The Ṛgveda clearly states that readers of the Vedas are not confused by the many Deities' names in the Vedas who control various regions and functions in the cycle of the cosmos.